Research on the impact of academic libraries – areas, methods, indicators. Issue 8 (11th November 2019) - Głowacka, Ewa
Abstract : Purpose: The purpose of this paper is to indicate the place of assessment of the impact of libraries in the overall quality evaluation of these institutions. In the paper, an attempt has been made to separate the concepts of the impact and values of library services and, according to the designated scope, the most important areas of research, methods and indicators for the assessment of the impact of academic libraries were characterized. The focus was on the most important areas, i.e. on the impact of libraries on didactics and academic research, information literacy and on its assessment in the cultural and environmental aspect. Design/methodology/approach: A literature-based overview of actual insights on tasks and areas, methods, indicators research on the impact of academic is provided. Findings: The author has determined that the analysis of the impact of academic libraries can mainly concern the following areas: information (influence on didactics, research and information competence of users), cultural and environmental. That is why it is worth analyzing the most important methods and indicators of research on the impact of academic libraries in these areas. The best way to research the quality of libraries, and especially to determine its impact on users and the environment, is to use a mixed methodology – a whole set of quantitative and qualitative methods and techniques. Triangulation can involve the use of both qualitative and quantitative data or the use of multiple methods to develop one type of data. Research limitations/implications: However, these methods were used to study the impact of academic libraries, whose results do not determine the financial value. Practical implications: The paper shows the methods of research on the quality of the functioning of academic libraries with a special emphasis on the study of their impact on users and the social environment. Social implications: The paper shows the methodology of determining the social role of academic libraries. Originality/value: The paper intends to add to the body of knowledge about the research methodology for the impact of academic libraries.